Web-based Seminar - New Source of Qualitative Study: Data Collection during the Pandemic of COVID-19 - Tiong, Wen Ni; Sim, Anne Freda Siaw Fen (SEISENSE Journal of Management, 2020)
Objective- This article aims to discuss the authors’ own experience using a web-based seminar (webinar) as a new data collection method for a qualitative descriptive study on factors influencing digital banking adoption among potential users in Malaysia (Digital Banking Study).   Design - This will be the first study to gather information from industry players and public perception towards digital banking service using webinars, with evidence compared to the study’s quantitative results.  Findings – Data derived from webinar sessions are consistent with the quantitative results, and the potential of its uses as a new research tool was discussed in detail. Policy Implications- The findings showed several practical implications that are potentially useful for researchers, academics, and business analysts to consider adopting webinar data as a new qualitative data collection method. Originality - This study documents the supporting evidence of the potential use of webinars as a useful tool to collect quality observation data.